(untitled) (Western European Journal of Medicine and Medical Science, 2025)
Nutrients play a fundamental role in supporting the vital functions and overall health of living organisms. They serve as the primary source of energy, building blocks for cellular structures, and regulators of biochemical processes essential for growth, repair, and maintenance of the body. This paper explores the classification of nutrients, including macronutrients and micronutrients, and highlights their specific functions in metabolism, immune response, and physiological regulation. Understanding the significance of balanced nutrient intake is crucial for preventing nutritional deficiencies and promoting optimal health. The study also examines the impact of nutrient imbalances on disease development and underscores the importance of nutrition in sustaining life and well-being